Forward–backward asymmetry of Drell–Yan lepton pairs in pp collisions at s?=8s=8TeV - Collaboration, C. M. S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Flechl, M.; et al. (My University, 2016)
A measurement of the forward–backward asymmetry AFB of oppositely charged lepton pairs (?? and ee) produced via Z / ?? boson exchange in pp collisions at ?s = 8 TeV is presented. The data sample corresponds to an integrated luminosity of 19.7 fb-1 collected with the CMS detector at the LHC. The measurement of AFB is performed for dilepton masses between 40 GeV and 2TeV and for dilepton rapidity up to 5. The AFB measurements as a function of dilepton mass and rapidity are compared with the standard model predictions. © 2016, CERN for the benefit of the CMS collaboration.
Citation: Collaboration, C. M. S., Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., . . . Woods, N. (2016). Forward–backward asymmetry of Drell–Yan lepton pairs in pp collisions at ?s = 8 TeV. European Physical Journal C, 76(6), 1-24. doi:10.1140/epjc/s10052-016-4156-z